2022
DOI: 10.1093/ce/zkac037
|View full text |Cite
|
Sign up to set email alerts
|

A review on non-isolated low-power DC–DC converter topologies with high output gain for solar photovoltaic system applications

Abstract: The major challenges of the high-gain DC–DC boost converters are high-voltage stress on the switch, extreme duty ratio operation, diode reverse-recovery and converter efficiency problems. There are many topologies of high-gain converters that have been widely developed to overcome those problems, especially for solar photovoltaic (PV) power-system applications. In this paper, 20 high-gain and low-power DC–DC converter topologies are selected from many topologies of available literature. Then, seven prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 132 publications
0
10
0
1
Order By: Relevance
“…However, it is found that the energy loss originating from the voltage mismatch for the optimized device is smaller than the internal loss of a commonly used DC-DC converter with an efficiency of 90%-95%. 58,59) In short, the direct connection yields a higher ( ) h .…”
Section: And N Nmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is found that the energy loss originating from the voltage mismatch for the optimized device is smaller than the internal loss of a commonly used DC-DC converter with an efficiency of 90%-95%. 58,59) In short, the direct connection yields a higher ( ) h .…”
Section: And N Nmentioning
confidence: 99%
“…This offers an advantage that precise design is not required because Although η DDC changes depending on the setting, it usually ranges from 90%-95%. 58,59) Thus, the direct connection of the VM tandem SC modules and EC modules yields higher η H2 and η CO than the use of the DDCs.…”
Section: Appendix Bmentioning
confidence: 99%
“…Furthermore, this enhancement plays a crucial role in improving the overall efficiency of electric propulsion systems. It also plays a significant part in supporting the electric mobility ecosystem's sustainability objectives [38,39]. The illustration below showcases the HG-QBC topology, highlighting its intricate architecture and its potential to bring about a significant transformation in energy conversion for electric automobiles.…”
Section: High-gain Quadratic Boost Converter Topologymentioning
confidence: 99%
“…These diverse factors collectively contribute to the dynamic efficiency variations observed across different operational scenarios. Ongoing research and developments in power electronics continue to refine and optimize converter efficiency over time [34][35][36][37].…”
Section: Power Converters and Mppt Algorithmsmentioning
confidence: 99%